The preparation of enantiopure cyanohydrins and their hydrogenations - Veum, L. (author) (2006)
This thesis deals with various enzyme-catalysed approaches towards enantiopure cyanohydrins, which are important building blocks in both the pharmaceutical and agricultural industry. Common for the methods that have been investigated is that enzymes were used in combination with chemical catalysts in cascade reactions, either in one pot or in consecutive reactions without isolation of the intermediates. Chapter 1 contains an overview of this work, emphasizing the importance of immobilising, either of the enzyme or of the chemical catalyst, for these cascades to be successful. The preparation of (S)-Î³,Î´-unsaturated cyanohydrins in a two-step cascade reaction from Î³,Î´-unsaturated alcohols is described in chapter 2. First the alcohol is oxidised to the corresponding aldehyde utilizing catalytic amounts of immobilised TEMPO, and PhI(OAc)2 as the stoichiometric oxidant. Due to the instability of the resulting aldehyde, the reaction mixture is used directly for the next step after filtering off the TEMPO and removing the acetic acid formed during the oxidation. The (S)-Î³,Î´-unsaturated cyanohydrins were obtained in a HbHNL-catalysed hydrocyanation of the aldehyde. Only by removing the TEMPO prior to the enzyme reaction, the products could be obtained in excellent optical purity. In chapter 3 a straightforward process for the encapsulation of HbHNL in sol-gels under low methanol conditions is developed. By adding a sol that was prepared by hydrolysis of TMOS/MTMS at pH 2.8 with continuous removal of methanol to a stirred solution of the enzyme in a buffer at pH 6.5, at least 65 % of the activity of the free enzyme could be recovered after the encapsulation. These aquagels were successfully used in the synthesis of (S)-cyanohydrins. Although the recycling of the gels failed, the method holds great potential for the encapsulation of other methanol sensitive enzymes. Chapter 4 describes a straightforward process for the preparation of optically active protected cyanohydrins. Lipase B from Candida antarctica (CALÂB) ...